Development of an integrated vaccine system (IVS) for vaccination healthcare database - Mohd Azrul Hisham, Mohd Adib; Muhammad Shahminan, Lukman; Nur Hazreen, Mohd Hasni (Centre for Advanced Research on Energy (CARe), 2019)
Hospital Information System or also recognized as a Healthcare Information System (HIS) is an integrated computer system installed throughout the hospital to expand the hospital clinical and administrative function. Nevertheless, the conservative guide method of recording vaccination information is less organized and problematic to be recovered back. IVS is an integrated information technology system that efforts to address the weaknesses in the conventional method by organizing storage for vaccination information and also mobile application to remind the parents of the next vaccination date. IVS is immobile in the initial development thru positive progress.